2022
DOI: 10.3389/fphar.2021.754807
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Liver Fibrosis Activity and the Potential Mode of Action of Ruangan Granules: Integrated Network Pharmacology and Metabolomics

Abstract: Ruangan granules (RGGs) have been used to treat liver fibrosis with good clinical efficacy for many years. However, the potential mechanism of action of RGGs against liver fibrosis is still unclear. In this study, we evaluated the quality and safety of this preparation and aimed to explore the anti-liver fibrosis activity and potential mode of action of RGGs using network pharmacology and metabolomics. The results showed that RGGs contained abundant ferulic acid, salvianolic acid B and paeoniflorin, and at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The UHPLC-Q-Orbitrap HRMS analysis of TFPCP revealed the presence of 14 flavonoids, including quercetin, taxifolin, pinocembrin, and luteoloside, among others. Many of these flavonoids exhibit a wide range of pharmacological properties, such as antioxidant, antiinflammatory, and antimicrobial effects (Chirumbolo and Bjorklund, 2018;Shang et al, 2021). In this study, we provided further evidence that TFPCP can ameliorate liver injury and fibrosis.…”
Section: Discussionmentioning
confidence: 52%
“…The UHPLC-Q-Orbitrap HRMS analysis of TFPCP revealed the presence of 14 flavonoids, including quercetin, taxifolin, pinocembrin, and luteoloside, among others. Many of these flavonoids exhibit a wide range of pharmacological properties, such as antioxidant, antiinflammatory, and antimicrobial effects (Chirumbolo and Bjorklund, 2018;Shang et al, 2021). In this study, we provided further evidence that TFPCP can ameliorate liver injury and fibrosis.…”
Section: Discussionmentioning
confidence: 52%
“…Wang and colleagues [ 27 ] have demonstrated that stimulation of HSCs by PDGF leads to cell proliferation and exacerbate fibrogenesis. In another study, Liu and colleagues [ 28 ] examined the protective effects of isorhamnetin in preventing the progression of liver fibrosis induced by carbon tetrachloride (CCl 4 ) in mice. They measured the expression of Smad3 and p38 mitogen-activated protein kinase proteins using Western blotting.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic fibrosis, as a crucial pathological feature, exists in almost all chronic liver diseases triggered by hepatitis virus, alcoholism, cholestasis and lipodystrophy, etc ( Shang et al, 2022 ). Without appropriate therapy, hepatic fibrosis could further deteriorate into cirrhosis, portal hypertension and hepatocellular carcinoma ( Anuja et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%